Do Differences in Levels, Types, and Duration of Muscle Contraction Have an Effect on the Degree of Post-exercise Depression? - Miyaguchi, Shota; Kojima, Sho; Kirimoto, Hikari; Tamaki, Hiroyuki; Onishi, Hideaki (Frontiers in Human Neuroscience, 2016)
We conducted two experiments to determine how differences in muscle contraction levels, muscle contraction types, and movement duration affect degree of post-exercise depression (PED) after non-exhaustive, repetitive finger movement. Twelve healthy participants performed repetitive abduction movements of the right index finger at 2.0 Hz. In experiment 1, we examined the effects of muscle contraction levels at 10%, 20%, and 30% maximum voluntary contraction and the effects of muscle contraction types at isotonic and isometric contraction. In experiment 2, we examined the effects of movement duration at 2.0 and 6.0 min. Motor-evoked potentials (MEPs) were recorded from the right first dorsal interosseous muscle before movement tasks and 1–10 min after movement tasks. MEP amplitudes after isotonic contraction tasks were significantly smaller than those after isometric contraction tasks and decreased with increasing contraction levels, but were independent of movement duration. This study demonstrated that the degree of PED after non-exhaustive repetitive finger movement depended on muscle contraction levels and types. Thus, the degree of PED may depend on the levels of activity in the motor cortex during a movement task. This knowledge will aid in the design of rehabilitation protocols.